Determination of folates in vegetables and their retention during boiling - Marie HOLASOVÁ; Vlasta FIEDLEROVÁ; Slavomíra VAVREINOVÁ (Czech Journal of Food Sciences, 2008)
HPLC method for 5-methyltetrahydrofolate (5-MTHF) determination in vegetables was optimised for the folate release from the food matrix. Enzymatic hydrolyses using the subsequent addition of α-amylase, protease, and conjugase from hog kidney, or their combinations, were tested. The highest release values were obtained with the application of enzymes α-amylase and conjugase, amounting to 112.4-127.0% of the values obtained in the processing with sole conjugase. The simultaneous addition of both enzymes and the incubation at pH 4.9 did not suppress the release of folates. Spinach, Chinese cabbage, lettuce, cauliflower, and broccoli contained more than 50 μg of 5-MTHF/100g, whereas less than 25 μg/100 g was found in potatoes, carrot, white cabbage, green and yellow pepper. Individual vegetables differed in the folate retention during their boiling under constant conditions. The highest retention was found in Brussels sprouts, cauliflower, and broccoli. After 8 min boiling more than 75% of the initial amount of 5-MTHF remained in these vegetables. Lower values of 5-MTHF retention, between 37% and 52% of their initial content, were found in spinach, savoy cabbage, and carrot.